2012
DOI: 10.1002/pip.2302
|View full text |Cite
|
Sign up to set email alerts
|

Empirical assessment of short‐term variability from utility‐scale solar PV plants

Abstract: Variability of solar power is a key driver in increasing the cost of integrating solar power into the electric grid because additional system resources are required to maintain the grid's reliability. In this study, we characterize the variability in power output of six photovoltaic plants in the USA and Canada with a total installed capacity of 195 MW (AC); it is based on minute‐averaged data from each plant and the output from 390 inverters. We use a simple metric, “daily aggregate ramp rate” to quantify, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 27 publications
4
64
0
Order By: Relevance
“…While the PDFs of single-sensor observations all exhibit such tails, these features are much less prominent for the spatially averaged k * increment distributions. This result is consistent with previous findings of e.g., Lave and Kleissl (2010), Marcos et al (2011b), Dyreson et al (2014), andvan Haaren et al (2014). Comparing the distributions of increments from multiple pyranometers and PV plants of different capacities for various temporal resolutions, these previous studies all showed high magnitude changes with increasing time lag, and fewer high magnitude changes with increasing PV plant size (or numbers of sensors).…”
Section: Increment Statisticssupporting
confidence: 82%
See 3 more Smart Citations
“…While the PDFs of single-sensor observations all exhibit such tails, these features are much less prominent for the spatially averaged k * increment distributions. This result is consistent with previous findings of e.g., Lave and Kleissl (2010), Marcos et al (2011b), Dyreson et al (2014), andvan Haaren et al (2014). Comparing the distributions of increments from multiple pyranometers and PV plants of different capacities for various temporal resolutions, these previous studies all showed high magnitude changes with increasing time lag, and fewer high magnitude changes with increasing PV plant size (or numbers of sensors).…”
Section: Increment Statisticssupporting
confidence: 82%
“…While overcast conditions may necessitate other power sources to substitute the momentary lack of PV generation, clear and mixed conditions can negatively impact the electrical grid. Under clear conditions, high PV power feedback (i.e., reverse power flow from the distribution grid to the transmission grid) can occur and needs to be managed in areas of high PV penetration (Wirth et al, 2014), whereas mixed conditions may endanger the grid's reliability due to the frequent power ramping of PV systems (van Haaren et al, 2014). In the context of subminute variability, we illustrate the event risk of k * fluctuations by means of increment PDFs in Fig.…”
Section: Variability In Spatial Averagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Wind power and solar PV power have stochastic, volatile and uncertain characteristics, and biomass power often has a fuel shortage issue. The large-scale penetration of renewable energy power will have certain impacts on multiple stakeholders in China's electric power system, including power generation enterprises, power grid companies, electricity consumers and the environment, as well as society in general [33][34][35][36]. The detailed impacts are analyzed below.…”
Section: Impacts Analysis Of Renewable Energy Power Accessing the Powmentioning
confidence: 99%